ENDOSCOPIC SPECTRUM OF OESOPHAGEAL FINDINGS PRESENTING WITH DYSPHAGIA - Naveed, Shabnam; Nageen, Ayesha; Rani, Priyanka; Ahmed, Syed Masroor; Ali, Zeeshan (Pakistan Journal of Physiology, 2021)
Background: The causes of dysphagia may represent chronic benign disorders to life threatening oesophageal neoplasia. The first line investigation in evaluation of dysphagia is upper gastrointestinal endoscopy. The objective of the study was to observe the oesophageal endoscopic findings in patients presenting with dysphagia and their correlation with age and gender. Methods: This cross-sectional study was conducted in Jinnah Postgraduate Medical Centre, Karachi, from 2017 to 2019. Adult patients who had their chief complaint as dysphagia underwent endoscopy and their findings were noted on a pre-designed proforma. The findings were analysed on SPSS-22. Results: Out of 242, patients, males were 102 (42%) and females were 140 (58%). Among them 19 (8%) were in the age group of 18–20 years, 103 (42.5%) between the ages of 21–40 years, 81 (33.5%) in the ages of 41–60 years and 39 (16%) in the age group of 61 years and above. Pharyngeal growth was seen in 27 (11%) patients. The commonest pathology in oesophagus was oesophageal growth (58, 24%). With respect to age group, oesophagitis was more common between the ages 18–20 years while oesophageal growth was more prevalent in all age groups above 18 years. With respect to gender, oesophageal web/stricture was twice more in females while the oesophageal growth frequency was nearly equal in both genders. Conclusion: There is high frequency of oesophageal growth among all age groups and is alarming. In patients with dysphagia, endoscopic evaluation for early detection is crucial.